Oral Bacteriotherapy in Patients With COVID-19: A Retrospective Cohort Study - Ceccarelli, Giancarlo; Borrazzo, Cristian; Pinacchio, Claudia; Santinelli, Letizia; Innocenti, Giuseppe Pietro; Cavallari, Eugenio Nelson; Celani, Luigi; Marazzato, Massimiliano; Alessandri, Francesco; Ruberto, Franco; Pugliese, Francesco; Venditti, Mario; et al. (Frontiers in Nutrition, 2021)
Background: Mounting evidence suggests SARS-CoV-2 may impact on host microbiota and gut inflammation, infecting intestinal epithelial cells. This possible link and its implications can be investigated by observing the effects of modulation of the microbial flora in patients with COVID-19. The aim of this study was to compare the rate of mortality, the need of ICU hospitalization and the length of hospitalization in patients with severe COVID-19 pneumonia who received the best available therapy (BAT) versus patients treated with BAT and supplemented with oral bacteriotherapy. Methods: This retrospective, observational cohort study included 200 adults with severe COVID-19 pneumonia. All patients received therapeutic regimens including low molecular weight heparin plus one or more between hydroxychloroquine, azithromycin, antivirals, and Tocilizumab. Oral bacteriotherapy was used as complementary treatment. Results Out of the 200 patients, 112 received BAT without oral bacteriotherapy and 88 BAT with oral bacteriotherapy. Crude mortality was 22%. 11% died in the group of patients treated with BAT plus oral bacteriotherapy versus 30% subjects in the group of patients managed only with BAT (p<0.001). By multivariate analysis, the age >65 years, CRP >41.8mg/L, Platelets <150.000mmc, and cardiovascular events were associated with the increased risk of mortality. Oral bacteriotherapy was an independent variable associated with a reduced risk for death. Despite large prospective trials are needed, this study highlights a possible role for oral bacteriotherapy in the management of patients hospitalized for COVID-19 pneumonia.